Development of an appropriate breeding scheme for tolerance to Empoasca kraemeri in common bean - Kornegay, Julia L.; Cardona, C. (1990)
Significant advances in increasing tolerance to the leafhopper Empoasca kraemeri Ross & Moore in common bean have been obtained using a new breeding scheme where yield under leafhopper attack is the principal selection criterion in the evaluation of progenies. However, to further refine this breeding scheme, a study was conducted to determine whether selection for nonprotected yield would be more effective in early versus late generations. Two selection strategies were compared. In Strategy I, early generation selections in the F2 and F3 were compared to Strategy II where late generation selections were made in the F4 and F5, with the F2 and F3 generations advanced using single pod descent and bulk practices, respectively. Yield trials of the F6 lines from both selection strategies were conducted under nonprotected and insecticide protected treatments. No significant differences were detected between the two selection strategies. However, Strategy II did produce advanced lines with greater nonprotected yields than did Strategy I, with the best F6 line, in three out of four crosses, coming out of Strategy II. Late generation selection is recommended over early generation selection. Results of the new leafhopper breeding scheme, based on yield, are compared to the old breeding scheme where selections were made using visual selection practices in early generations.